Enhanced carbon dioxide conversion at ambient conditions via a pore enrichment effect - Zhou, Wei; Deng, Qi-Wen; Ren, Guo-Qing; Sun, Lei; Yang, Li; Li, Yi-Meng; Zhai, Dong; Zhou, Yi-Hong; Deng, Wei-Qiao (Nature communications, 2020)
Chemical fixation of carbon dioxide (CO 2 ) may be a pathway to retard the current trend of rapid global warming. However, the current economic cost of chemical fixation remains high because the chemical fixation of CO 2 usually requires high temperature or high pressure. The rational design of an efficient catalyst that works at ambient conditions might substantially reduce the economic cost of fixation. Here, we report the rational design of covalent organic frameworks (COFs) as efficient CO 2 fixation catalysts under ambient conditions based on the finding of “pore enrichment”, which is concluded by a detailed investigation of the 10994 COFs. The best predicted COF, Zn-Salen-COF-SDU113, is synthesized, and its efficient catalytic performance for CO 2 cycloaddition to terminal epoxide is confirmed with a yield of 98.2% and turnover number (TON) of 3068.9 under ambient conditions, which is comparable to the reported leading catalysts. Moreover, this COF achieves the cycloaddition of CO 2 to 2,3-epoxybutane under ambient conditions among all porous materials. This work provides a strategy for designing porous catalysts in the economic fixation of carbon dioxide. Currently the cost of CO 2 chemical fixation remains high because of harsh reaction conditions. Here, the authors report a covalent organic framework screened from 10994 candidates as the efficient CO 2 fixation catalyst under ambient conditions based on the finding of a “pore enrichment effect”.